Training on the Folklore Nasi Menangis as a Form of Oral Tradition Appreciation, Food Waste Mitigation, and Mindful Eating Habituation for the Parents of Students at SD Negeri 01 Ngijo, Semarang - Muzakki Bashori; Wasino Wasino; Meddiati Fajri Putri; Inez Kalyana Azmi; Abdul Rozaq; Herlina Putri Khawismaya; Rahma Danisa Eka Safitri (Universitas Negeri Semarang, 2024)
This community service program aims to conduct storytelling training on the folklore